PENGARUH SUKU BUNGA DAN NILAI TUKAR RUPIAH (KURS) TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) (PERIODE TAHUN 2020 - 2022) - Albertus Kukuh Yudi Pratama,; Hasim As’ari, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
This study aims to determine effect of interest rates and exchange rates on the Composite Stock Price Index (JCI) for the period 2020-2022. The results of hypothesis testing show that together the variables of Interest Rates and Rupiah Exchange Rates (exchange rates) have a significant effect on the Composite Stock Price Index (JCI) for the period 2020-2022. Partially, interest rates and exchange rates simultaneously have a significant effect on the Composite Stock Price Index (JCI). From the analysis of the coefficient of determination, it is known that interest rates and exchange rates affect the Composite Stock Price Index (JCI) by 40.6%, while the remaining 59.4% is influenced by other variables outside this research model